INTERCULTURAL COMMUNICATION IN LEARNING AND TEACHING FOREIGN LANGUAGES (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article gives the reader information about linguo-cultural teaching and learning, besides that, it provides with the ways of effective intercultural communication.